Simulated hatching failure predicts female plasticity in extra-pair behavior over successive broods. (5th October 2018) - Yuta, Teru; Nomi, Daisuke; Ihle, Malika; Koizumi, Itsuro
Abstract : Female birds are expected to alter their mating behavior based on information from previous breeding attempts. Using a field experiment, we show that female birds become more promiscuous when they find their eggs do not hatch. The number of offspring sired by extra-pair males increased in the second broods after simulated hatching failure in the first breeding attempts. This finding contributes to our understanding of the adaptive significance of female multiple mating. Abstract: Although many studies have investigated the occurrence of extra-pair paternity (EPP) and its adaptive significance in wild population of birds, we still know surprising little about the plasticity in mating behavior of females at the individual level and how it affects the patterns of paternity. To address this question, we focused on the direct fertility benefit hypothesis for the function of EPP and studied if female birds react in extra-pair mating behavior after reproductive failures using a wild population of the Japanese great tit, Parus minor, a socially monogamous passerine with a moderate frequency of EPP and a high-multiple brooding rate. We simulated hatching failure by replacing with artificial eggs during the egg laying period to investigate whether females subsequently altered their mating behavior and became more promiscuous to improve reproductive success in their following clutches. The proportion of extra-pair offspring per clutches of both experimental and control pairs increased in the second clutches (replacement and repeat), but compared with the control pairs, the increase in the experimental pairs was significantly greater. The present study suggests that individual females appear to be making decisions based on specific cues and flexibly altering mating behavior in adaptive ways. Also, our results are compatible with one of the long-debated hypotheses for the evolutionary maintenance of EPP which predicts that females gain direct fitness benefit through increased reproductive success from mating multiply.